2007
DOI: 10.1136/oem.2006.028803
|View full text |Cite
|
Sign up to set email alerts
|

Effects of training to implement new working methods to reduce knee strain in floor layers. A two-year follow-up

Abstract: Objectives: Follow-up study after two years to measure the effects of an implementation strategy consisting of information, education and training in the use of new tools and working-methods for the purpose of reducing knee strain and knee complaints in floor layers. Methods: Training of floor layers (n = 292) in using new working methods was evaluated by questionnaires during the courses. Two years later, this follow-up included questionnaires for the course participants (n = 216) and a control group of floor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 9 publications
2
15
0
1
Order By: Relevance
“…Multidimensional ergonomic interventions, including a participatory approach and individual, technical and organisational measures, seem to be an appropriate strategy for reducing the physical demands and the symptoms of MSDs,1 2 but evidence of their efficacy is still limited 3. Nevertheless, the scientific understanding of the aetiology of MSDs and their work-relatedness is sufficient to implement effective preventive interventions,1 2 4 as demonstrated by the study of Jensen and Friche5 published in this issue ( see page ). The study provides interesting insights into the prevention of musculoskeletal (knee) disorders and the strategy to implement interventions in a specific trade—that is, floor and carpet fitters (floor layers)—in daily practice.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Multidimensional ergonomic interventions, including a participatory approach and individual, technical and organisational measures, seem to be an appropriate strategy for reducing the physical demands and the symptoms of MSDs,1 2 but evidence of their efficacy is still limited 3. Nevertheless, the scientific understanding of the aetiology of MSDs and their work-relatedness is sufficient to implement effective preventive interventions,1 2 4 as demonstrated by the study of Jensen and Friche5 published in this issue ( see page ). The study provides interesting insights into the prevention of musculoskeletal (knee) disorders and the strategy to implement interventions in a specific trade—that is, floor and carpet fitters (floor layers)—in daily practice.…”
mentioning
confidence: 99%
“…Their intervention consisted of providing new working tools to allow performance of tasks in an upright posture to reduce the time spent in a kneeling position,6 which they hypothesised would reduce knee disorders. The implementation strategy followed a complex process including scientific research, information for employees, employers and trade unions, training, and participatory ergonomics with direct involvement of workers to develop and implement new working methods for floor layers 5 6. The results showed a positive effect of training to introduce new working methods and change workers’ behaviour during floor laying.…”
mentioning
confidence: 99%
“…However, many of the studies included in the review suffered from methodological shortcomings (ie, lack of a proper randomization procedure or a lack of a control group), making their findings at risk for bias. Several randomized controlled trials (RCT) have been conducted to evaluate the effectiveness of PE as a strategy to prevent MSD and/or to reduce MSD-related pain (16)(17)(18)(19). However, no RCT on PE has specifically focused on LBP and NP prevention.…”
mentioning
confidence: 99%
“…Probably because of the low implementation rate of the prioritised ergonomic measures, the ergocoaches played a less effective role than expected. However, Jensen and Friche showed that a participatory ergonomics programme in combination with an implementation strategy (ie, information about ergonomics and training in ergonomic skills) resulted in sustainable reductions in severe knee problems among Danish floor layers 40. Based on the findings of our process evaluation in which participatory ergonomics appeared to be a successful method to prioritise risk factors and develop and prioritise ergonomic measures,21 and the promising findings of Jensen and Friche, we still believe that participatory ergonomics has the potential to reduce workers′ exposure to occupational risk factors.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%